ESTE scale validation to measure loneliness in adult population - Cardona Jiménez, Jairo León; Villamil Gallego, María Mercedes; Henao Villa, Eucaris; Quintero Echever, Ángela (Investigación y Educación en Enfermería, 2010)
<!– [if gte mso 9]> <![endif]–><!– [if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]–><!– [if gte mso 9]> <![endif]–><!– [if gte mso 10]> <![endif]–> Objective. To validate the loneliness measurement scale ESTE in adult population who assist to third age groups in Bello (Colombia). Methodology. Cross sectional descriptive study. Internal consistency, reproducibility and behavior were assessed using demographic variables. The sample consisted of 180 adults aged 55 or over belonging to 15 senior groups selected randomly from the 100 registered in Bello at the time of the study execution. Results. The factorial analysis of the scales’ four main components explained 55.9% of the variance. Factors that explain greater variance are: adaptation crisis (17.2%), marriage loneliness (14.0%), and social loneliness (13.9%). Family loneliness was the factor that less explained (10.9%). Cronbach Alfa scale reliability of 0.9, being in each of the factors above 0.7. The test-retest reproducibility measured by the Sperman correlation coefficient was 0.88. Conclusion. ESTE scale validation indicates that it can be used as an adult loneliness measurement instrument in Colombia’s adult population.